A Methodology for Measuring and Monitoring Congested Corridors: Applications in Manhattan Using Taxi GPS Data. Issue 4 (2nd October 2018) - Qing, Carson; Hao, Wei
ABSTRACT: This paper describes how the Taxi Passenger Enhancement Program (TPEP) Trip Record data can be used to measure traffic congestion along selected corridors in Manhattan. Two corridors in the rapidly changing Far West Side, Ninth Avenue and Tenth Avenue, were selected for analysis in this case study. This paper will describe a methodology using GIS applications that can visualize and identify trends in traffic conditions over time along corridors selected for analysis. This methodology can be applied to evaluate and monitor congested corridors in response to changes in land use patterns, policy decisions, and various temporary conditions affecting street operations.